Association of higher-risk alcohol consumption with injecting paraphernalia sharing behaviours in intravenous drug users. (March 2014) - Wang, Mei; Shen, Jiucheng; Deng, Yuan; Liu, Xianling; Li, Jianhua; Wolff, Kim; Finch, Emily
Abstract Background: Alcohol use is common among injecting drug users. The coexistence of alcohol consumption and injecting risk behaviour has the potential to increase harms among intravenous drug users (IDUs). Objective: This study aimed to determine whether the level of alcohol use is a risk factor for injecting paraphernalia sharing behaviours. Methods: A total of 637 treatment-seeking IDUs were assessed for injecting paraphernalia sharing behaviours and drinking risk level as defined by the National Institute for Health and Care Excellence (NICE). Multivariate analyses were performed to identify alcohol risk factors associated with injecting paraphernalia sharing behaviours. Results: After adjusting for the effects of ethnicity, employment and drug used, the odds ratio of higher risk drinking for injecting paraphernalia sharing behaviours was 1.92 (95% CI 1.31–2.83). Conclusion: Higher-risk drinking in IDUs is associated with higher rates of injecting paraphernalia sharing behaviours. It is important to take alcohol use into account when evaluating these patients for treatment and designing intervention strategies.